Perancangan Mesin Produksi Pelet Terapung - Din Aswan Amran Ritonga; Sarjana Sarjana; Rahmad Dwi Sandi (JITEKH, 2022)
This design is based on the results of observations and literature studies, precisely for fish farming feed. Fish feed is always there, but has a relatively expensive price. Especially as a fish farmer, must have alternatives to develop his business. Because there is no use of a floating pellet molding machine, the machine was designed as a solution. Usually this machine is only used in pellet molding from fine bran and frementation materials that have been specifically designed to make animal feed. This design is carried out to make pellet printers from bran and calculate the production capacity. The design results use a 1450 rpm electric motor, 1:50 gear box, conveyor tank with a length of 220 mm, die with a size of 2 and 4 mm and a thickness of 8 mm, a cutting knife with a thickness of 1 mm, a length of 35 mm with a speed of 9 rpm and produces a capacity of 18 kg / hour.